Musical Drama Audio Production for MI Asy Syifa Rancamanyar Teachers: Produksi Audio Drama Musikal bagi para Guru MI Asy Syifa Rancamanyar - Anwar, Ardy Aprilian; Fiandra, Yosa; Belasunda, Riksa (Universitas Lancang Kuning, 2024)
When celebrating graduation or promotion at school level, they are used to holding a celebration event all day long. Various types of competitions were held and competed in, and various artistic performances were shown openly. Performing arts include musical group performances, solo singing, dance, musical ensembles and musical drama. There are still several schools, including MI Asy Syifa Rancamanyar, which still use external assistance to prepare activities on the grounds that they donot have knowledge in the related field. For example, when creating singing accompaniment music, dance accompaniment music, and even audio for musical drama performances with a more complex level of complexity. This study aims to understand teachers who are involved in extracurricular activities, particularly their ability to create audio-musical dramas. The method used is service learning-based training with an active participatory approach that focuses on meeting the community needs identified in previous year's training. The research results indicate an improvement in participants' understanding and knowledge of the recording and audio rendering processes. This audio production training helps teachers gain a better understanding and trains them in audio production for musical dramas using Reaper DAW software. As a result, teachers become more productive and independent in preparing materials for art performances at their schools